A study in the recovery method of the directional controllability of single-rotor helicopters under tail-rotor damage conditions by using main-rotor brakes and the dead zone/disturbance simultaneous estimator - Daigo FUJIWARA (Nihon Kikai Gakkai ronbunshu, 2015)
This paper describes considerations of the effectiveness about the recovery control of the yaw rate motion of single-rotor helicopters by using both motors (engines) and main-rotor brakes in autorotation flight under tail-rotor damage conditions. First, the newly-developed main rotor brake unit for the experimental small helicopter is introduced. Flight test results show the yaw rate controllability by using the proposed brake and motor. Next, the yaw rate control system with a dead-zone estimator/compensator is designed to improve the control performance considering dead zones of input command signals of the brake or the motor. New method of dead-zone estimation when disturbances are applied to helicopters is proposed in this paper. This method is based on the nonlinear extended Kalman filter which enables simultaneous estimantion of dead zones and a yaw moment external disturbance by using a rotational speed of a main rotor in addition to a yaw rate for measurement updates of the estimator, which is designed based on the helicopter motion dynamics model including a clutch and a brake with motor dynamics. Estimation and control performances of the proposed system are validated through several simulation and flight test results.